Medien - Sprechen - Klang Empirische Forschungen zum medienvermittelten Sprechen - Bose, Ines; Finke, Clara Luise; Schwenke, Anna (Schriften zur Sprechwissenschaft und Phonetik, 2021)
This volume brings together empirical studies on language and speech as well as on their linkage with musical-sound elements in the media (radio, audio guide, audio book, radio play as well as YouTube and Instagram videos). The contributions are primarily concerned with auditory comprehensibility and sound aesthetics, with the medial target group and format specificity of radio genres and other media offerings, and with the speech effects of medial genres, also in cultural comparison. German and Russian news formats, standardized short moderations in several countries, gender constructions in double moderations of German radio primetime, soccer reports, audio guides for children, audio books read aloud and freely narrated, Instagram stories and Youtube educational videos, as well as hip-hop radio as educated radio will be examined. Ines Bose, Prof. Dr. phil. habil., is at the Department of Speech Science and Phonetics at Martin Luther University Halle-Wittenberg. Clara Luise Finke, Dr. phil., is head of the Department of Speech Science at the University of Leipzig. Anna Schwenke, Dr. phil., works at the University of Greifswald as a research assistant in the German Department of the Elementary School Teacher Training Program.